ENVIRONMENTAL EDUCATION OF PRESCHOOLERS (Journal of Science-Innovative Research in Uzbekistan, 2024)
the article considers an urgent problem of environmental  protection - the formation of the beginning of ecological culture in children; the  formation of a consciously correct attitude to objects and phenomena of nature; to  develop ecological thinking; training in practical actions for nature protection